Kepemimpinan Kepala Sekolah dalam Mengembangkan Kompetensi Guru di Sekolah Luar Biasa (SLB) Negeri Seduri Kecamatan Mojosari Kabupaten Mojokerto - Misbakhul Ulum (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Research on leadership in education always captures attention. Various leadership styles have been developed to enhance the quality of education. This study focuses on the role of school principals in improving teacher competence at SLB Negeri Seduri, which serves students with disabilities.Leadership in schools for students with disabilities differs from that in general schools, requiring specialized approaches and models due to distinct educational needs and cultures. This research will explore the contributions of the principal as both a leader and manager in developing teacher competence at SLB Negeri Seduri.With these two focuses, the study aims to provide insights into the principal’s role in developing educator competencies at SLB. The findings are expected to contribute both theoretically and practically to identifying effective leadership models for schools serving students with disabilities.The method employed is qualitative research, emphasizing deductive and inductive analysis as well as the dynamics of relationships between observed phenomena.The research findings indicate that the principal, as a leader, implements a visionary charismatic leadership style, serving as the executor of the school’s vision and mission, innovator, motivator, and effective communicator. As a manager, the principal combines three dimensions of communication: democratic in policy planning, authoritative in decision-making, and delegative based on teachers' competencies.Keywords: Leadership, Disabled, Competency, Teacher, Leader, Manager.